2007
DOI: 10.1021/jf070418h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Low-Density Polyethylene Film Containing Butylated Hydroxytoluene on Lipid Oxidation and Protein Quality of Sierra Fish (Scomberomorus sierra) Muscle during Frozen Storage

Abstract: Fresh sierra fish (Scomberomorus sierra) fillets were packed in low-density polyethylene films with butylated hydroxytoluene (BHT-LDPE) added. Fillets packed in LDPE with no BHT were used as controls (LDPE). The packed fillets were stored at -25 degrees C for 120 days in which the film released 66.5% of the antioxidant. The influence of the antioxidant on lipid and protein quality, lipid oxidation, muscle structure changes, and shear-force resistance was recorded. As compared to LDPE films, fillets packed in B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…ANTIDX 4% showed the best results in terms of maintaining muscle integrity after 120 days at -20 °C since it had a more compact and orderly distribution compared with that of the other treatments. Torres-Arreola et al (2007) found that the use of LDPE films containing BHT as antioxidant prevents the fracture and detachment of sierra fish muscle during frozen storage showing an association between lipid oxidation and the integrity of the muscle fibers. However, in the present study, such behavior was not clearly observed since there was no high level of lipid oxidation present.…”
Section: Scanning Electron Microscopymentioning
confidence: 96%
See 2 more Smart Citations
“…ANTIDX 4% showed the best results in terms of maintaining muscle integrity after 120 days at -20 °C since it had a more compact and orderly distribution compared with that of the other treatments. Torres-Arreola et al (2007) found that the use of LDPE films containing BHT as antioxidant prevents the fracture and detachment of sierra fish muscle during frozen storage showing an association between lipid oxidation and the integrity of the muscle fibers. However, in the present study, such behavior was not clearly observed since there was no high level of lipid oxidation present.…”
Section: Scanning Electron Microscopymentioning
confidence: 96%
“…However, one disadvantage of this technique is that the migration of the antioxidant to the muscle is not controlled. Thus, a practicable alternative is the use of plastic packaging containing antioxidants, which may retard lipid oxidation and protein denaturation under a controlled release of the antioxidants (Torres-Arreola et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial value of fish fillets stored at low temperatures may be affected because of the deterioration of its muscle due to lipid oxidation effect, causing both loss in flavor and damage in the product's texture (Pérez-Alonso et al, 2003;Aubourg et al, 2004), mainly in fat species such as sierra (Scomberomorus sierra) which contains about 10% lipids (Torres-Arreola et al, 2007), with moderate levels of n-3 fatty acids, namely, eicosapentaenoic acid and docosahexaenoic acid (Murillo et al, 2014). Fatty acids present in this species are highly susceptible to oxidation, this often determines the type of handling, storage, distribution and shelf life of the product (Leland, 1997;Losada et al, 2004;Aubourg et al, 2005;Rodríguez et al, 2007;Chaouqy et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Films with added antioxidants have been used in order to prevent the sierra's muscle oxidation during freezing. Torres-Arreola et al (2007) studied the effect on lipid oxidation of sierra fillets packaging with a film of low density polyethylene containing butylhydroxytoluene, finding a positive effect of the antioxidant material on the quality of the fillets assessed during frozen storage (4 months). However, the fillets were stored at -25 ° C immediately after the capture of the animal, which is not common during the daily handling of the product by fishermen and traders.…”
Section: Introductionmentioning
confidence: 99%